Upaya Pengembangan Manajemen Sumber Daya Manusia pada Pesantren sebagai Kelembagaan Islam - Yusuf, Dodi Muhammad; Jamilus, Jamilus (Peneliti.net, 2024)
The development of human resources is needed by Islamic institutions such as Islamic boarding schools so that they can compete in this competitive era and adapt to current developments. Therefore, this research aims to study the concepts and efforts to develop human resources in Islamic boarding schools as Islamic institutions. This research method is in the form of a literature review or library research by utilizing secondary data to be used as data in research language. The findings show that efforts to develop human resource management within the Islamic boarding school can be carried out in a number of stages, namely job analysis, recruitment, selection, training and development, motivation, commitment, job satisfaction and performance assessment. The process of developing resource management is the same as for organizations and companies in general, where in Islamic boarding schools the differences only lie in the elements that form the Islamic boarding school, namely Kyai, Santri, Dormitory or Pondok, Mushola, and yellow book studies. This means that the process of managing human resources is carried out by the leadership of the Islamic boarding school, namely Kyai, who has strong religious provisions and is obeyed by all members of the Islamic boarding school. At Islamic boarding schools, it is hoped that Kyai can develop human resource management optimally so that Islamic boarding schools can produce a generation of quality students with a conducive Islamic boarding school climate and have a competitive advantage compared to other educational institutions.